1995
DOI: 10.1093/carcin/16.5.985
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos is involved in the cellular defence against the genotoxic effect of UV radiation

Abstract: The proto-oncogene c-fos encodes a nuclear protein that forms together with c-Jun or other members of the Jun family the transcription factor AP-1. The c-fos gene is inducible by UV radiation and other DNA damaging treatments which may indicate that it is required in defence against DNA damaging agents. To address this hypothesized function of c-Fos, we have compared the response of mouse fibroblasts deficient in c-Fos with the corresponding wild-type cells towards the genotoxicity of UV radiation. It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…Wt cells were exposed to 0 or 7.5 UV-C in the presence or absence of 1 mM actinomycin D for 3 or 6 h. Total RNA was isolated and RT-PCR was performed using fen1 or, as positive control, gapdh-specific primers To see whether Fen1 is also inducible in other rodent cell lines, we assayed 3T3 and f20 mouse fibroblasts: both are p53 proficient (data not shown). A line isogenic to f20 is f10, which expresses mutated p53 (Haas and Kaina, 1995, and data not shown). In the lines expressing wt p53, Fen1 increased after UV-C light exposure, whereas in f10 cells no increase was observed (Figure 5b,upper panel).…”
Section: Expression Of Fen1 Upon Uv-c Exposurementioning
confidence: 90%
See 2 more Smart Citations
“…Wt cells were exposed to 0 or 7.5 UV-C in the presence or absence of 1 mM actinomycin D for 3 or 6 h. Total RNA was isolated and RT-PCR was performed using fen1 or, as positive control, gapdh-specific primers To see whether Fen1 is also inducible in other rodent cell lines, we assayed 3T3 and f20 mouse fibroblasts: both are p53 proficient (data not shown). A line isogenic to f20 is f10, which expresses mutated p53 (Haas and Kaina, 1995, and data not shown). In the lines expressing wt p53, Fen1 increased after UV-C light exposure, whereas in f10 cells no increase was observed (Figure 5b,upper panel).…”
Section: Expression Of Fen1 Upon Uv-c Exposurementioning
confidence: 90%
“…f10 cells are not only mutated in p53 but also deficient for c-Fos. Previously we reported that c-fos knockout cells (both established and primary fosÀ/À cell lines) are hypersensitive to UV-C light (Haas and Kaina, 1995;Lackinger and Kaina, 2000;Lackinger et al, 2001). Therefore, we were interested to learn whether c-Fos deficiency impacts Fen1 induction.…”
Section: Expression Of Fen1 Upon Uv-c Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Activation of transcription factors by DNA damage directly enhances/represses the transcription of their targeted genes, which can exert biological functions in cellular responses. Several transcription factors, such as p53, c-Myc, AP-1 (c-jun and c-fos) and Oct-1, have been characterized to play important roles in the control of cell cycle checkpoints, apoptosis and signaling transduction pathways (Amundson et al, 1998;Haas and Kaina, 1995;Hollander and Fornace, 1989;Jin et al, 2001;Kastan et al, 1992;Kumari and Alvarez-Gonzalez, 2000;Rupnow et al, 1998;Tong et al, 2001;Yu et al, 2002;Zhan et al, 1994a;Zhao et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that c-fos plays a protective role against the cytotoxic effects of cadmium. Since c-fos-deficient cells were sensitive to hexavalent chromium 43) , UV [44][45][46] , ionizing radiation 46) and DNA-damaging agents 46,47) , c-fos may be involved in cellular protective functions, especially against genotoxic stresses including heavy metals.…”
Section: ) Toxicity Of Cadmium In Fibroblasts Lacking C-fosmentioning
confidence: 99%